The Relationship Among Diabetes Stigma, Anxiety, Depression, and Diabetes Self-Care in Individuals with Type 2 Diabetes - Meryem Gamze Simsek; Sevecen Çelik Ince (Caring: Indonesian Journal of Nursing Science, 2024)
Diabetes-related anxiety, depression, and stigma have a greater impact on individuals with type 2 diabetes than the condition itself. Studies examining the stigma of diabetes together with depression, anxiety, and self-care are quite limited in the literature.  The purpose of this study is to determine the relationship between diabetes stigma, anxiety, depression, and diabetes self-care in individuals with type 2 diabetes. This study utilized a cross-sectional, correlational methodology. The sample for this study included 200 individuals with type 2 diabetes. Data collection included the Patient Information Form, the Type 2 Diabetes Stigma Assessment Scale, the Hospital Anxiety and Depression Scale, and the Diabetes Self-Care Scale. Data were analyzed using the student t-test, one-way ANOVA, Bonferroni post hoc test, and Pearson correlation analysis. There was a positive, moderate, and statistically significant relationship between the total score of the diabetes stigma assessment scale and anxiety score (r=0.488, p<0.01), as well as a positive, moderate, and statistically significant relationship between the total score and depression score (r=0.464, p<0.01). There was a positive, very weak, and significant relationship between diabetes self-care and the total score (r=0.144, p<0.05). There was a positive, very weak, and statistically significant relationship between the total score of the Diabetes Self-Care Scale and depression score (r=0.159, p<0.05), whereas there was no statistically significant relationship with anxiety score (p>0.05). Diabetes self-care in individuals with type 2 diabetes is influenced by diabetes stigma, anxiety, and depression. It is recommended to plan evidence-based studies that aim to reduce these factors through experimental designs.